Marketing Mix Analysis of Interest in Buying Products Wardah Cosmetics at Wardah Outlet Suzuya Mall Rantauprapat - Rambe, Ayu Nurzannah Rambe Nurzannah; Simanjorang, Elida Florentina Sinaga; Syahputra, Rizki (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Cosmetics are very important to enhance their appearance, whether for a work look or engaging in daily activities. The purpose of this study is to determine the effect of product, price, location, and promotion on buying interest in Wardah cosmetics. This research was conducted at the Outlet Wardah Suzuya Mall Rantauprapat. This research is quantitative with a population of 100 people, sampling using a saturated sampling technique where the entire population in the study is used as a sample. The results showed that there was an effect of product, price, promotion, and location on the intention to buy Wardah cosmetics with a large influence of 81.8%, and the remaining 18.2% was explained by other factors outside the variables used in this study. Other factors referred to include taste, customer loyalty, customer satisfaction, facilities, word of mouth, service quality, and so on.